Peningkatan Life Skills Melalui Pembelajaran IPA Pendekatan Scientific Pada Siswa MI - Ummu Khairiyah (Universitas Islam Lamongan, 2017)
This study is aimed at improving Life Skills through the application of scientific approach. The stages of this study is to analyze the problems in school, develop scientific approach-based learning tools, and use learning tools. The subjects of this study were 30 MI students on the environmental pollution subject matter. In this study, data collection techniques used qualitative and quantitative descriptive analysis. The results showed that life skills consisting of thinking skills, academic skills and social skills increased after being given an activity through science teaching based on a scientific approach.Keywords: life skills, scientific approach, learning tools